Biological Correlates of Empathy - E. Timucin Oral; Kursat Altınbas; Sinan Guloksuz; Serap Ozcetinkaya (Psikiyatride Güncel Yaklaşımlar, 2010)
Empathy can be defined as the capacity to know emotionally what another is experiencing from within the frame of reference of that other person and the capacity to sample the feelings of another or it can be metaphorized as to put oneself in another’s shoes. Although the concept of empathy was firstly described in psychological theories, researches studying the biological correlates of psychological theories have been increasing recently. Not suprisingly, dinamically oriented psychotherapists Freud, Kohut, Basch and Fenichel had suggested theories about the biological correlates of empathy concept and established the basis of this modality decades ago. Some other theorists emphasized the importance of empathy in the early years of lifetime regarding mother-child attachment in terms of developmental psychology and investigated its role in explanation of psychopathology. The data coming from some of the recent brain imaging and animal model studies also seem to support these theories. Although increased activity in different brain regions was shown in many of the brain imaging studies, the role of cingulate cortex for understanding mother-child relationship was constantly emphasized in nearly all of the studies. In addition to these studies, a group of Italian scientists has defined a group of neurons as “mirror neurons” in their studies observing rhesus macaque monkeys. Later, they also defined mirror neurons in human studies, and suggested them as “empathy neurons”. After the discovery of mirror neurons, the hopes of finding the missing part of the puzzle for understanding the biological correlates of empathy raised again. Although the roles of different biological parameters such as skin conductance and pupil diameter for defining empathy have not been certain yet, they are going to give us the opportunity to revise the inconsistent basis of structural validity in psychiatry and to stabilize descriptive validity. In this review, the possible neurobiological background of empathy will be discussed in the light of the recent brain imaging and animal studies.